Pengaruh Emotional Dissonance, Emotional Intelligence, dan Emotional Exhaustion Terhadap Service Sabotage - Meisandi Arya; Charles Mercelie; Netania Emilisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this research is to determine the description of the employees of the Grand Mercure Hotel Kemayoran Jakarta, to determine and analyze the influence of Emotional Dissonance on Service Sabotage, to determine and analyze the influence of Emotional Intelligence on Service Sabotage, and to determine and analyze the influence of Emotional Exhaustion on Service Sabotage. The population in this study were all employees of the Grand Mercure Hotel Kemayoran Jakarta. In this research, a quantitative method approach was used with a survey and a sample of 225 people was obtained using a purposive sampling technique. Survey research is carried out by distributing questionnaires. Previously, the questionnaire was tested for validity and reliability first. The data analysis technique in this research uses descriptive analysis and linear regression analysis. Description of the employees of the Grand Mercure Hotel Kemayoran Jakarta, most of whom are male, most employees are under 35 years old, and most employees have worked at the hotel for 0-2 years. The results of this research explain that Emotional Dissonance has a positive and significant effect on Service Sabotage with p-value of 0.012. Emotional Intelligence has a negative and significant effect on Service Sabotage with p-value of 0.023. Emotional Exhaustion has a positive and significant effect on Service Sabotage with p-value of 0.045.